Alterations in Red Blood Cells and Plasma Properties after Acute Single Bout of Exercise. (18th December 2013) - Gwozdzinski, Krzysztof; Pieniazek, Anna; Brzeszczynska, Joanna; Tabaczar, Sabina; Jegier, Anna
Abstract : The aim of this study was to investigate alterations in haemoglobin conformation and parameters related to oxidative stress in whole erythrocytes, membranes, and plasma after a single bout of exercise in a group of young untrained men. Venous blood samples from eleven healthy young untrained males (age = 22 ± 2 years, BMI = 23 ± 2.5 kg/m 2 ) were taken from the antecubital vein before an incremental cycling exercise test, immediately after exercise, and 1 hour after exercise. Individual heart rate response to this exercise was 195 ± 12 beats/min and the maximum wattage was 292 ± 27 W. Immediately after exercise, significant increase in standard parameters (haemoglobin, haematocrit, lactate levels, and plasma volume) of blood was observed as well as plasma antioxidant capacity one hour after exercise. Reversible conformational changes in haemoglobin, measured using a maleimide spin label, were found immediately following exercise. The concentration of ascorbic acid inside erythrocytes significantly decreased after exercise. A significant decline in membrane thiols was observed one hour after exercise, but simultaneously an increase in plasma thiols immediately after and 1 h after exercise was also observed. This study shows that a single bout of exercise can lead to mobilization of defensive antioxidant systems in blood against oxidative stress in young untrained men.